Post-operative evolution of gastrectomized patients: Statistic analysis - Rubinstein, Juan Pedro; Bazzini, Mario; Boccoleri, Silvana; Barreiro, Javier; Waserstein, Moisés (Cirugía del Uruguay, 1982)
The study includes 386 patients who were gastrectomized at the HosPital de Clínicas between the years 1970 and 1979. Of these, 59,33 % were operated on because of gaetric ulcer and 35, 75% because of duoudenal ulcer. More than 50% of ali the cases were operated on due to complications of their ulcerous disease, being the digestive helllorrhage the most frequent. There was a clear prevailence of the masculine sex, between 40 and 65 years of age. Evolution was unknown, but presumed to be good in 47,93% the cases; it was confirmed to be good in 24,35%; fair with minor complications in 9,84% and bad with maior complications or ulcerous relapse in 12,44%. Global mortality was 5.44%.